Pengaruh Kualitas Penerapan GCG (Good Corporate Governance) dan Struktur Modal Terhadap Kinerja Keuangan Perbankan Syariah Periode 2016-2020 - Yunita, Wanda; Fatoni, Ahmad (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2025)
This study is based on previous research and phenomena that still show gaps and inconsistencies, making further investigation necessary to provide novelty. The focus of this research is to analyze how Good Corporate Governance (GCG) through the audit committee, board of commissioners, managerial ownership, and capital structure affects the sharia-based financial performance of banks in Indonesia during 2016–2020. GCG mechanisms such as the audit committee and board of commissioners play a vital role in supervising financial statement preparation, decision-making, and evaluation, which directly influence company performance. Meanwhile, capital structure represents the balance between debt and equity as sources of funding for operational activities. This study uses secondary data obtained from annual reports of Islamic commercial banks listed on the Indonesia Stock Exchange (IDX) and the Sharia Banking Statistics (SPS) published by the Financial Services Authority (OJK). The analysis method applied is multiple linear regression, supported by classical assumption tests to ensure validity and reliability of results. The research sample was selected using purposive sampling to represent relevant criteria. Data processing was conducted using EViews version 12 software to obtain accurate and comprehensive findings.